DIRECTIONS FOR IMPROVING THE FINANCING OF INNOVATIVE ACTIVITIES OF TEXTILE ENTERPRISES - Samaroxonov Asqarxon Jamolxon oʻgʻli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The textile industry plays a vital role in the economic development of many countries by contributing significantly to employment, exports, and GDP growth. However, in the era of rapid technological change and increasing global competition, textile enterprises are increasingly required to adopt innovative approaches to maintain competitiveness, enhance productivity, and ensure sustainable development. Despite the recognized importance of innovation, the financing of innovative activities remains a major challenge for many textile enterprises, particularly in developing economies. This is due to several structural and systemic constraints such as limited access to credit, insufficient public and private investment, and weak institutional support mechanisms.